Indoxyl sulfate induces left ventricular hypertrophy via the AhR-FGF23-FGFR4 signaling pathway - Kishimoto, Hiroshi; Nakano, Toshiaki; Torisu, Kumiko; Tokumoto, Masanori; Uchida, Yushi; Yamada, Shunsuke; Taniguchi, Masatomo; Kitazono, Takanari (Frontiers in Cardiovascular Medicine, 2023)
Background Patients with chronic kidney disease (CKD) have a high risk of left ventricular hypertrophy (LVH). Fibroblast growth factor 23 (FGF23) and indoxyl sulfate (IS) are associated with LVH in patients with CKD, but the interactions between these molecules remain unknown. We investigated whether IS contributes to LVH associated with FGF23 in cultured cardiomyocytes and CKD mice. Methods and results In cultured rat cardiac myoblast H9c2 cells incubated with IS, mRNA levels of the LVH markers atrial natriuretic factor, brain natriuretic peptide, and β-myosin heavy chain were significantly upregulated. Levels of mRNA of the polypeptide N-acetylgalactosaminyltransferase 3 (GALNT3), which regulates FGF23 O-glycosylation, and FGF23 were also upregulated in H9c2 cells. Intact FGF23 protein expression and fibroblast growth factor receptor 4 (FGFR4) phosphorylation were increased in cell lysates by IS administration. In C57BL/6J mice with heminephrectomy, IS promoted LVH, whereas the inhibition of FGFR4 significantly reduced heart weight and left ventricular wall thickness in IS-treated groups. While there was no significant difference in serum FGF23 concentrations, cardiac FGF23 protein expression was markedly increased in IS-injected mice. GALNT3, hypoxia-inducible factor 1 alpha, and FGF23 protein expression was induced in H9c2 cells by IS treatment and suppressed by the inhibition of Aryl hydrocarbon receptor which is the receptor for IS. Conclusion This study suggests that IS increases FGF23 protein expression via an increase in GALNT3 and hypoxia-inducible factor 1 alpha expression, and activates FGF23-FGFR4 signaling in cardiomyocytes, leading to LVH.